Data mining of adverse drug event signals with Nirmatrelvir/Ritonavir from FAERS. - Ji Sun; Xuanyu Deng; Juanjuan Huang; Gefei He; Shiqiong Huang (PLoS ONE)
Nirmatrelvir/Ritonavir, acting as an effective agent against COVID-19, has achieved considerable results in clinical studies in terms of drug efficacy. However, there is little research about its medication safety. Based on the FDA adverse event reporting system (FAERS) database, this study aims to mine the adverse reaction signals of the latest major recommended drug Nirmatrelvir/Ritonavir for the antiviral treatment of COVID-19, so as to provide a basis for safe and rational drug use. The reporting odds ratio (ROR) was used to explore the adverse event report data of all COVID-19 emergency use authorization (EUA) products in the FAERS database with the deadline of third quarter of 2023. In the analysis, 135427 adverse drug event (ADE) reports were found, and 35250 ADEs were reported with Nirmatrelvir/Ritonavir as the primary suspected drug, which was involved in multiple system. There was a high signal intensity of dysgeusia (ROR = 72.98), diarrhea (ROR = 3.03) and headache (ROR = 1.25), which was compatible with the adverse reactions recorded in the manual for Nirmatrelvir/Ritonavir. In addition, it was suggested that Nirmatrelvir/Ritonavir might cause pale-colored stools (ROR = 45.53), chromaturia (ROR = 3.07), yellow skin (ROR = 3.62), tongue coating (ROR = 35.55) and other new adverse reactions (not included in the instructions manual for Nirmatrelvir/Ritonavir). The ADEs of Nirmatrelvir/Ritonavir that are not in the instructions and are highly relevant in the real world are supplemented, prompting clinical attention to the ADEs of the drug, and providing a theoretical basis for the safe and effective application of the drug.